Digital Literacy and Digital Transformation for Digital Entrepreneurship: Review with Contextual Implications for the Online Deposit Service (Jastip) Business - Minda Muliana Sebayang; Warsani Purnama Sari; Asmawati Laia; Octavia Vernitasari Saragih; May Sarah Nasution (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid growth of the digital economy has encouraged the development of digital entrepreneurship, including the online deposit services business (commonly in Indonesia known as jastip). This study applies the Systematic Literature Review (SLR) method following the PRISMA 2020 protocol to examine the role of digital literacy and digital transformation in the development of digital entrepreneurship. Literature was searched in Science Direct using a combination of keywords related to digital literacy, digital transformation, and digital entrepreneurship, published between 2021 and 2025. Of 60 articles initially identified 53 remained after 7 duplicate records were removed. Following title/abstract screening, 15 records were excluded for not being research articles and/or not being relevant to the topic, leaving 38 articles assessed for full-text eligibility. Of these, 27 were further excluded for not fully addressing the topics under analysis, resulting in 11 articles that met all inclusion criteria and were analyzed. The results show that digital literacy strengthens business actors' ability to adopt and utilize digital technology, while digital transformation drives operational efficiency, innovation, and competitiveness. These findings are then discussed in relation to the online deposit service business as a contextual implication rather than as a direct empirical finding, since none of the reviewed articles specifically examined jastip or personal-shopper businesses. Business actors are advised to strengthen digital literacy, the government is encouraged to support training, infrastructure, and regulation, and future researchers are recommended to test these relationships empirically within the online deposit service context.